What ‘Corona War’ metaphor means in Iranian political discourse - Aliakbar Imani (Penerbit Universiti Kebangsaan Malaysia, 2021)
Political leaders’ discourse plays a significant role in directing the public opinion during crises. Hence, this study analyzed 71 speeches delivered by Hassan Rouhani, President of Iran (2013- 2021), during the first and the second waves of COVID-19 pandemic (February 20 till August 30, 2020) as the most critical period of the pandemic attack. This study drew upon Lakoff & Johnson’s (1980) Conceptual Metaphor Theory as its theoretical background, and the analysis of the speeches was comprised of metaphor identification using the Metaphor Identification Procedure (MIP) and metaphor interpretation. The findings of the study reveal employment of metaphorical representations of coronavirus as a discursive strategy to deal with the situation. The main metaphorical representation of coronavirus was framing public cooperation and national solidarity during the COVID-19 pandemic as participating in a war. As argued in this paper, the employed metaphors not only remained loyal to general war features, but they also entailed a specific sociocultural image of war for the Iranian people based on their experience and memories of the eight-year Iran-Iraq war. Finally, this study recommends for future studies to include the specific sociocultural context and historical background of the addressed audience. This provides further insight into what metaphors specifically mean to the addressed audience, which is beyond general metaphor use. This study is hoped to be a small step towards bringing into spotlight the significance of sociocultural aspects and historical background as necessary information to provide in-depth insights into what makes metaphors effective communicative tools to specific audience.